Plan de comercialización asociativa para los pequeños productores de cacao en el cantón Quinsaloma provincia de Los Rios, año 2018 - Castillo Bone, Monica Kennys (2018)
Commercialization is a set of activities conducted by organizations and a determined social process, whereby it is considered in two definitions; the first term is micro-commercialization which observes customers directly and also to the activities of the organization in an individual way. And the second one, macro-commercialization that considers the production and distribution system widely. It is considered appropriate carry out a thorough study about the associativity of the cocoa producers in the canton Quinsaloma, since they present difficulty not only in selling the product, but also in the process of harvest and post-harvest of it. To realize this research work was used a survey as an instrument of gathering information that was directed to the cocoa producers in the canton as an object of the study, who are the ones involved directly in this investigative work. By means of the collection of information, it was possible stablish the analysis of the results, and then set a proposal in based to the PESTLE analysis, which will permit design a commercialization plan in order to improve the sale of the product in the canton Quinsaloma in Los Rios province